2022
DOI: 10.3390/mti6050031
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Development of Sense of Presence and Cybersickness during an Immersive VR Experience

Abstract: Following the advances in modern head-mounted displays, research exploring the human experience of virtual environments has seen a surge in interest. Researchers have examined how to promote individuals’ sense of presence, i.e., their experience of “being” in the VE, as well as to diminish the negative side effects of cybersickness. Studies investigating the relationship between sense of presence and cybersickness have reported heterogeneous results. Authors that found a positive relation have argued that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The meta-review of Weech et al [21] argues that the relationship is negative and that studies finding positive associations are explainable by the confounding variable of immersion. A recent study by [48] gave evidence for this theory. By continuously measuring the association of cybersickness and sense of presence, the authors found simultaneous measurements in time to explain the positive association.…”
Section: Association Of Big Five Personality Traits With Cybersicknes...mentioning
confidence: 92%
“…The meta-review of Weech et al [21] argues that the relationship is negative and that studies finding positive associations are explainable by the confounding variable of immersion. A recent study by [48] gave evidence for this theory. By continuously measuring the association of cybersickness and sense of presence, the authors found simultaneous measurements in time to explain the positive association.…”
Section: Association Of Big Five Personality Traits With Cybersicknes...mentioning
confidence: 92%
“…Conversely, a meta-review by Weech et al (2019) posits a negative correlation between the two constructs, arguing that positive associations are explainable by the covariate of immersion. Thorp et al (2022) found that the development of SoP and SS follow a similar temporal development, positively correlating throughout the experiment. The authors propose that covariates such as immersion, excitement, engagement, or CL similarly impact SS and SoP, explaining the positive relationship.…”
Section: The Interplay Between CL Sop and Ssmentioning
confidence: 62%
“…In another study [9], the relation between cybersickness and repeated exposure to the VR environment may end up in the reduction of cybersickness for certain VR contents. In [10], the cybersickness and presence experienced in a VR environment are found to have a temporal relationship. In [11], the presence and cybersickness are shown to be related to the dynamic FoV, where the restriction of dynamic FoV can reduce the cybersickness and improve the presence in a VR environment.…”
Section: Presence Quality and Cybersickness In Virtual Realitymentioning
confidence: 97%
“…The complex relation between presence and cybersickness is difficult to understand. There are various studies [7][8][9][10][11][12][13][14][15][16][17] that model the relation between the presence and cybersickness in a VR environment [7]. In general, the presence and cybersickness have an inverse relationship.…”
Section: Presence Quality and Cybersickness In Virtual Realitymentioning
confidence: 99%